Сatalytic activity of Mn-containing loaded systems in reaction of carbon monooxide oxidation: UDС 541.128.13 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
Catalytic activity in CO oxidation of Mn-containing systems, loaded at the carriers of various chemical nature was investigated. It was established, that the difference in activity of catalysts with high metal content (10 wt.% Mn, formed at 500 0С can results by temperature interval of precursor's decomposition during catalytic reaction and various character of Mn(NO3)2 decomposition at the definite temperature. It was found that 10 % Mn-ZSM-5 system has the higher activity among catalysts 10 % Mn-carriers, formed at 500 0С.
Keywords: -